Methods for preparing Li-PS products and corresponding products

By using a mixture of Li4P2S6, Li2S and sulfur to heat in an inert atmosphere, the problem of using unstable reagents and the need for protection of the atmosphere in the prior art is solved, a safe and simple synthesis process is achieved, and the high ionic conductivity of Li7P3S11 product is maintained.

CN114402402BActive Publication Date: 2025-04-08SPECIALTY OPERATIONS FRANCE SAS +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080062577.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-06
Filing Date
2020-09-04
Publication Date
2025-04-08
Estimated Expiration
2040-09-04

AI Technical Summary

Technical Problem

In the prior art, the preparation of Li-P-S product Li7P3S11 with high ionic conductivity requires the use of unstable Li2S and P2S5 reagents, and requires working in a protective atmosphere, which has problems of safety and operation difficulties.

Method used

The mixture of Li4P2S6, Li2S and sulfur was heated in an inert atmosphere and Li7P3S11 was synthesized by mechanochemical reaction, avoiding the use of unstable reagents and simplifying the operation process.

Benefits of technology

The possibility of storing Li4P2S6 in the drying chamber is realized, the dependence of the stability of the reagent on operation is reduced, the safety of the process and the simplicity of operation are improved, and the product of Li7P3S11 with high ionic conductivity is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114402402B_ABST
    Figure CN114402402B_ABST
Patent Text Reader

Abstract

The present invention relates to a novel process for preparing Li-P-S products, as well as products obtainable by said process, and their use, in particular as solid electrolytes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a novel process for preparing Li-PS products, as well as products obtainable by said process, and their use, in particular as solid electrolytes. Background Art

[0002] Lithium batteries are used to power portable electronics and electric vehicles due to their high energy and power density. Conventional lithium batteries utilize a liquid electrolyte consisting of lithium salts dissolved in an organic solvent. Since organic solvents are flammable, the above system creates safety issues. Lithium dendrites form and pass through the liquid electrolyte medium, causing short circuits and generating heat, which can cause accidents and lead to serious injuries.

[0003] Non-flammable inorganic solid electrolytes offer a solution to the safety issue. In addition, their mechanical stability helps suppress lithium dendrite formation, prevent self-discharge and heating issues, and extend the battery life.

[0004] Solid sulfide electrolytes are advantageous for lithium battery applications due to their high ionic conductivity and mechanical properties. These electrolytes can be pelletized and attached to electrode materials by cold pressing, which eliminates the necessity for high-temperature assembly steps. Eliminating the high-temperature sintering step removes one of the challenges of using lithium metal anodes in lithium batteries.

[0005] Therefore, new solid sulfide electrolytes are needed.

[0006] Li7P3S 11 It is a Li-PS product with very high Li+ conductivity (1.4x10 -3 Scm -1 )(Y.Seino, T.Ota, K.Takada, A.Hayashi, M.Tatsumisago, A sulphide lithium superion conductor is superior to liquid ion conductors for use in rechargeable batteries, Energy Environ. Sci. 7 (2014) 627-631). However, until today, the product has been prepared by a process that requires the use of Li2S and P2S5 as reagents, which are chemically unstable in the ambient atmosphere. Summary of the invention

[0007] The object of the present invention is to provide a new solid electrolyte, in particular comprising Li7P3S 11 .

[0008] Another object of the present invention is to provide a method for preparing a Li-PS product such as Li7P3S 11 The new method does not require the use of Li2S and P2S5 as reagents separately.

[0009] Another object of the present invention is to provide a method for preparing a Li-PS product such as Li7P3S 11 The new method does not require working in a protective atmosphere during the entire process.

[0010] Therefore, the present invention relates to a method for preparing a Li-PS product, the method comprising at least the following steps:

[0011] (a) mixing at least Li4P2S6, Li2S and sulfur to obtain a first mixture;

[0012] (b) heating the first mixture in an inert atmosphere, under vacuum or under a flow of H2S, and at a temperature and for a period of time sufficient to produce the Li-PS product; and

[0013] (c) Cooling and optionally pulverizing the Li-PS product.

[0014] This method is a new synthetic route for the synthesis of important solid sulfide electrolytes, especially the metastable glass-ceramic Li7P3S 11 , which has a very high Li+ conductivity (as mentioned above, 1.4 x 10 -3 Scm -1 ).

[0015] In contrast to existing reaction pathways that only require the use of Li2S and P2S5 as reagents, which are chemically unstable in ambient atmosphere, this method uses a Li-PS compound (i.e., Li4P2S6) as a precursor for synthesizing another Li-PS compound (i.e., the aforementioned Li7P3S 11 ) reagent. The main advantage of this particular reaction is that it facilitates the synthesis of Li7P3S 11 Previously, it was possible to use Li4P2S6 as a storage material in a dry chamber, whereas conventional reagents Li2S and P2S5 need to be stored in a protected atmosphere, such as Ar or N.

[0016] definition

[0017] Throughout this specification, unless the context dictates otherwise, the words "comprise" or "include", or variations such as "comprises", "comprising", "includes", "including", will be understood to mean the inclusion of the stated elements or method steps or groups of elements or method steps but not the exclusion of any other elements or method steps or groups of elements or method steps. According to a preferred embodiment, the words "comprise" and "include", and variations thereof mean "consisting only of".

[0018] As used in this specification, the singular forms "a", "an" and "the" include plural forms unless the context clearly indicates otherwise. The term "and / or" includes the meanings of "and", "or" and also includes all other possible combinations of the elements connected to the term.

[0019] The term "between" should be understood to include the limit values.

[0020] Ratios, concentrations, amounts, and other numerical data may be expressed in range form herein. It should be understood that this range form is used only for convenience and brevity and should be flexibly understood to include not only the numerical values ​​explicitly stated at the limits of the range, but also all single numerical values ​​or sub-ranges encompassed within the range, just as each numerical value and sub-range are explicitly stated. For example, a temperature range of about 120°C to about 150°C should be understood to include not only the explicitly stated limits of about 120°C to about 150°C, but also sub-ranges, such as 125°C to 145°C, 130°C to 150°C, etc., and a single amount within the specified range, including small quantities, such as, for example, 122.2°C, 140.6°C, and 141.3°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 : Comparison of the XRD patterns of the simulated pattern of Li4P2S6 [1], the synthesized Li4P2S6 (Example 1), and the ball-milled product of Reaction 1 (Example 2).

[0022] Figure 2 : Synthesized Li4P2S6 (Example 1), ball milled product of reaction 1 (Example 2), crystalline Li7P3S formed by annealing Example 2 11 (Example 3) and crystalline Li7P3S synthesized from conventional reagents Li2S and P2S5 11 Comparison of Raman spectra.

[0023] Figure 3 : Crystalline Li7P3S synthesized by reaction 1 11 (Example 3) Crystalline Li7P3S synthesized from conventional reagents Li2S and P2S5 11 , and Li7P3S 11 Comparison of XRD patterns of simulated patterns

[11] .

[0024] Figure 4 : Crystalline Li7P3S synthesized by reaction 1 11 (Example 3) Comparison of XRD patterns of an empty sample holder equipped with Be.

[0025] Figure 5 : Results of curve fitting for Examples 4 and 3. The Bragg positions are indicated by black vertical lines, the fits are plotted as black solid lines, and the collected data are indicated as black hollow spheres. The regions marked with asterisks are omitted from the fits because they involve contributions from the sample holder, as shown in Figure 4 shown.

[0026] Figure 6 : Structural part PS4 in the Raman spectrum from Example 3 3- 、P2S7 4- and P2S6 4- The relative ratios of the peak areas are also noted in the upper left corner of the figure.

[0027] Figure 7 : Structural part PS4 in the Raman spectrum from Example 4 3- 、P2S7 4- and P2S6 4- The relative ratios of the peak areas are also noted in the upper left corner of the figure.

[0028] Figure 8 : Ball milling product of reaction 1 (Example 2), crystalline Li7P3S synthesized by reaction 1 11 (Example 3) Crystalline Li7P3S synthesized from conventional reagents Li2S and P2S5 11 Comparison of ionic conductivity value and inverse temperature (1 / T).

[0029] Fig. 9 : Ball milling product of reaction 1 (Example 2), crystalline Li7P3S synthesized by reaction 1 11 (Example 3) Crystalline Li7P3S synthesized from conventional reagents Li2S and P2S5 11 σx T values ​​versus the inverse of temperature (1 / T). The linear fit used to calculate the slope of the line is also shown as a solid black line. DETAILED DESCRIPTION

[0030] Thus, the process of the present invention yields a Li-PS product, ie, a product comprising lithium (Li), phosphorus (P) and sulfur (S).

[0031] According to an embodiment, the Li-PS product is selected from the group consisting of: Li7P3S 11 , Li3PS4, Li7PS6 and / or Li 9.6 P3S 12 .

[0032] More preferably, the Li-PS product is Li7P3S 11 .

[0033] As mentioned above, step (a) of the process according to the invention comprises the preparation of a first mixture from Li4P2S6, Li2S and sulfur.

[0034] Such steps are achieved by implementing common means well known to those skilled in the art.

[0035] Preferably, step (a) comprises a chemo-mechanical or mechano-chemical reaction.

[0036] Then, according to step (b), the mixture is heated in an inert atmosphere, under vacuum or under a flow of H2S, and at a temperature and for a period of time sufficient to produce a Li-PS product.

[0037] As mentioned above, step (b) can be carried out in an inert atmosphere or under vacuum. When this step is carried out under a flow of H2S, step (b) may also include an additional sulfur source.

[0038] This heating step is carried out by implementing conventional means well known to the skilled person, such as using a sealed quartz tube, a batch furnace or a rotary furnace capable of operating under a flow of argon, nitrogen or H2S.

[0039] According to an embodiment, the temperature in step (b) is comprised from 150°C to 600°C, preferably from 180°C to 220°C.

[0040] According to an embodiment, the heating in step (b) is performed over a period of time comprised from 1 hour to 200 hours, such as from 6 hours to 200 hours.

[0041] Step (c) comprises cooling the product obtained after step (b). Preferably, the product is cooled until it reaches room temperature. This cooling step is carried out by implementing common means well known to the skilled person, such as, for example, by lowering the furnace at a rate of 5°C / min at room temperature.

[0042] In particular, the cooling is performed under natural cooling for a sufficient time to obtain a cooling product having a temperature of about room temperature. In the present invention, room temperature is defined as about 25°C ± 2°C.

[0043] The method of the present invention may also include an additional pulverization step. This step is performed after the cooling step. This pulverization step is performed by implementing common means known to the skilled person, such as, for example, by crushing the sample in a mortar, or applying a low-energy deagglomeration step.

[0044] Then, after step (c), the Li-PS is recovered by any means known to the skilled person, such as, for example, sieving the powder.

[0045] According to an embodiment, the Li4P2S6 added in step (a) is obtained from the reaction between Li2S and P2S5. Such reactions are well described in the prior art and are well known to the skilled person, for example, as described in (Solid State Ionics, 178 (2007), pp. 837-841) for high temperature solid state reactions.

[0046] The present invention also relates to a Li-PS product obtainable by the process as defined above.

[0047] As mentioned above, the Li-PS product is selected from the group consisting of: Li7P3S 11 , Li3PS4, Li7PS6 and / or Li 9.6 P3S 12 Preferably, therefore, the present invention relates to Li7P3S obtainable by the process as defined above 11 .

[0048] Implementation of the process of the present invention gives Li7P3S 11 The specific product has a crystal structure different from that of Li7P3S obtained by the method of the prior art. 11 of the crystal structure.

[0049] Therefore, the present invention also relates to a Li7P3S 11 A product having a crystalline structure and a volume V per formula unit comprised between 407 and 412 cubic angstroms at room temperature, as measured by X-ray diffraction.

[0050] X-ray diffraction (XRD) measurements are performed, for example, in a D8 Bruker diffractometer using Bragg-Brentano geometry with CuK-alpha radiation. Preferred measurement conditions are 15 seconds per 0.03 degree step.

[0051] The volume V of each formula unit is determined using the unit cell (lattice) parameters collected for a powder sample at standard atmospheric pressure (101325 Pa).

[0052] The volume V per formula unit is the lattice volume V' divided by the number of formula units in the unit cell Z, and Z is equal to 2 (Solid State Ionics, 178 (2007), pp. 1163-1167).

[0053] As is well known, V' is derived from the unit cell (lattice) parameters (a, b, c, α, β, γ).

[0054] V'=abcsqrt(1+2cosα.cosβ.cosγ-cos 2 α-cos 2 β-cos 2 γ)

[0055] (a, b and c are (in Angstroms is the length of the side (in units), and α, β and γ are the angles (in degrees) between them.

[0056] According to an embodiment, the present invention has the formula Li7P3S 11 The product may also contain an amorphous phase.

[0057] Preferably, the present invention has the formula Li7P3S 11 The product is a product in which the lattice (unit cell) parameters of the crystal structure measured by X-ray diffraction are as follows:

[0058] According to curve fitting

[0059] According to curve fitting

[0060] According to curve fitting

[0061] According to an embodiment, the present invention has the formula Li7P3S 11 The product is a product in which the lattice (unit cell) parameters of the crystal structure measured by X-ray diffraction are as follows:

[0062] -α=103.30°, according to curve fitting

[0063] -β=113.25°, according to curve fitting

[0064] -γ=75.07°, according to curve fitting

[0065] The invention also relates to the use of the product as defined above, alone or in combination with any crystalline or amorphous conductive Li material, as a solid electrolyte.

[0066] Preferably, the present invention relates to a compound having the formula Li7P3S as defined above 11The product, in particular having a crystalline structure and a volume V per formula unit comprised between 407 and 412 cubic angstroms at room temperature (as measured by X-ray diffraction), is used solely as a solid electrolyte.

[0067] According to an embodiment, the product can be used in combination with any crystalline or amorphous conductive Li material, such as, for example, β-Li3PS4 or glassy Li3PS4.

[0068] The invention also relates to a solid electrolyte comprising at least one product as defined above.

[0069] Preferably, the solid electrolyte according to the present invention comprises a solid electrolyte having the formula Li7P3S as defined above. 11 The product, in particular, has a crystalline structure and a volume V per formula unit comprised between 407 and 412 cubic angstroms at room temperature, as measured by X-ray diffraction.

[0070] The present invention also relates to a battery, preferably a lithium battery, comprising at least a Li-PS product obtainable by the process of the present invention or a Li7P3S 11 A product having a crystalline structure and a volume V per formula unit comprised between 407 and 412 cubic angstroms at room temperature, as measured by X-ray diffraction.

[0071] The battery using the product of the present invention may be a lithium ion or lithium metal battery.

[0072] The battery consists of a positive electrode and a negative electrode with an electroactive material that can reversibly intercalate and deintercalate lithium ions.

[0073] In the case of forming a positive electrode, the active material can be selected from the group consisting of: a composite metal chalcogenide represented by the general formula LiMY2, wherein M represents at least one transition metal substance such as Co, Ni, Fe, Mn, Cr, Al and V; and Y represents a chalcogen element such as O or S. Among these, a lithium-based composite metal oxide represented by the general formula LiMO2 is preferably used, wherein M is the same as above. Preferred examples thereof may include: LiCoO2, LiNiO2, LiNi x Co 1-x O2(0 <x<1)、Lix(Ni 0.8 Co 0.15 Al 0.05 )O2、Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 )O2、Li(Ni 0.6 Co 0.2 Mn 0.2 )O2、Li(Ni 0.8 Co 0.1Mn 0.1 )O2 and spinel structured LiMn2O4 and LiMn 1.5 Ni 0.5 O4. These active materials can be coated with inorganic or organic coatings, such as LiNbO3.

[0074] As an alternative, also in the case of forming a positive electrode, the active material may include a material having the nominal formula AB(XO4) f E 1-f A lithiated or partially lithiated transition metal oxyanion-based electrode material, wherein A is lithium, which may be partially replaced by another alkali metal accounting for less than 20% of the A metal; B is a major redox transition metal selected from Fe, Mn, Ni or a mixture thereof at an oxidation level of +2, which may be partially replaced by one or more additional metals, the one or more additional metals being at an oxidation level between +1 and +5 and accounting for less than 35% of the major +2 redox metal, including 0; XO4 is any oxygen anion, wherein X is P, S, V, Si, Nb, Mo or a combination thereof; E is a fluoride anion, a hydroxide anion or a chloride anion; f is the mole fraction of the XO4 oxygen anion, generally included between 0.75 and 1.

[0075] The active material used to form the positive electrode may also be sulfur or Li2S.

[0076] In the case of forming a negative electrode, the active material may preferably contain a carbon-based material and / or a silicon-based material and / or lithium metal

[0077] In some embodiments, the carbon-based material may be, for example, graphite such as natural or artificial graphite, graphene, or carbon black.

[0078] These materials may be used alone or as a mixture of two or more thereof.

[0079] The carbon-based material is preferably graphite.

[0080] The silicon-based compound may be one or more selected from the group consisting of silicon, silicon carbide, and silicon oxide.

[0081] Lithium metal can be used as lithium foil or lithium powder.

[0082] Examples

[0083] The present disclosure will now be illustrated with working examples, which are intended to illustrate the working of the present disclosure and are not intended to be used restrictively to imply any limitation on the scope of the present disclosure. Other examples within the scope of the present disclosure are also possible.

[0084] Example 1:

[0085] Li2S and P2S5 (both produced by Sigma-Aldrich) were used as starting materials. In a glove box filled with Ar, 1.5g of the total powder was placed in a 45mL ZrO2 bottle containing 12 ZrO2 balls (3 grams / ball, 10mm in diameter) at a molar ratio of 2:1. The bottle was sealed with Scotch tape and sealing film to prevent air exposure, then removed from the glove box and placed in a Fritzch planetary micromill 7. It was ball milled at a speed of 510RPM for 38 hours, with a rest of 15 minutes for every 15 minutes of grinding to prevent the bottle from overheating. The bottle was then moved to a glove box filled with Ar to recover the powder. The resulting white powder was then granulated at 530MPa with a mold having a diameter of 6mm. The pellets were vacuum sealed in a carbon-coated quartz tube, and the tube was then heated to 350°C at a heating rate of 5°C / min and kept at the same temperature for 36 hours. After the annealing step, the tube was slowly cooled to room temperature and opened in an Ar-filled glove box.

[0086] Example 2:

[0087] 400 mg of Example 1, 46 mg of sulfur and 22 mg of Li2S (produced by Sigma-Aldrich) were mixed in an Ar-filled glove box to balance the following reaction:

[0088] Reaction 1:

[0089] 3Li4P2S6+3S+Li2S=2Li7P3S 11

[0090] The mixture was placed in a 45 mL ZrO2 bottle containing 8 ZrO2 balls (3 g / ball, 10 mm in diameter). The bottle was sealed with Scotch tape and sealing film to prevent air exposure, then removed from the glove box and placed in a Retsch PM200 planetary ball mill. It was ball milled at a speed of 510 RPM for 76 hours, with a 15 minute rest for every 15 minutes of grinding to prevent the bottle from overheating. The bottle was then moved to a glove box filled with Ar to recover the powder.

[0091] Example 3:

[0092] Example 2 was pelletized at 530 MPa using a 6 mm diameter die. The pellets were vacuum sealed in a carbon-coated quartz tube, and the tube was then annealed at 200°C for 84 hours. After the annealing step, the tube was slowly cooled to room temperature and opened in an Ar-filled glove box to recover the sample.

[0093] Example 4 (comparison):

[0094] Li2S and P2S5 (both produced by Sigma Aldrich) were used as starting materials. In a glove box filled with Ar, 1.5g of the total powder was placed in a 45mLZrO2 bottle containing 12 ZrO2 balls (3 grams / ball, 10mm in diameter) at a molar ratio of 7:3. The bottle was sealed with Scotch tape and sealing film to prevent air exposure, then removed from the glove box and placed in a Fritzch planetary micromill 7. It was ball milled at a speed of 510RPM for 76 hours, while grinding for 15 minutes every 5 minutes to prevent the bottle from overheating. The bottle was then moved to a glove box filled with Ar to collect the powder. The resulting white powder was granulated at 530MPa with a mold having a diameter of 10mm. The pellets were vacuum sealed in a carbon-coated quartz tube, and the tube was then annealed at 200°C for 168 hours. After the annealing step, the tube was slowly cooled to room temperature and opened in a glove box filled with Ar.

[0095] Characterization Tools:

[0096] X-ray diffraction of the samples was collected using a Bruker D8 diffractometer at room temperature with Cu Kα radiation. Prior to the experiment, the samples were sealed in a sample holder equipped with Be in an Ar-filled glove box. Diffraction in the 2θ range of 10° to 100° was collected over 13 hours. The lattice parameters were determined by fitting the diffraction curves using Full-ProfSuite. The curve fitting procedures for Examples 3 and 4 were restricted to a shorter 2θ range (10° to 28°) to improve the accuracy of the fitting, as a large number of Bragg positions at higher angles in the P-1 space group could mislead the fitting process. The small peaks generated by the sample holder equipped with Be (see Figure 4 ) are removed before the fitting process to improve the accuracy of the fit.

[0097] Raman spectra were collected using a Raman DXR microscope (Thermo Fischer Scientific) with an excitation laser beam wavelength of 532 nm and a low laser power of 0.1 mW to prevent excessive heating of the sample. The fitting process was performed using Thermo Fisher Scientific's Omnic software.

[0098] Before the impedance spectrum measurement, the powder samples were cold pressed in an Ar-filled glove box. Examples 2 and 3 were pressed with a pressure of 530MPa using a mold with a diameter of 6mm, while Example 4 was pressed with a pressure of 530MPa using a mold with a diameter of 10mm. The pellets were then sandwiched between pre-dried carbon paper electrodes and then loaded into an airtight sample holder. The AC impedance spectrum was collected using a Biologic MTZ-35 frequency response analyzer. During the measurement, the excitation AC potential of all samples was set to 50mV. The frequency range of the measurement of Example 2 was 0.05Hz to 30MHz, while the range of 1Hz to 30MHz was applied in the measurement of Examples 3 and 4. The spectrum of each sample was recorded at a stable temperature value with a step size of 10°C between -30°C and 50°C. The ionic conductivity value was obtained by fitting the data to the equivalent circuit model using ZView software. The slope of the σT to 1 / T graph was used to determine the activation energy value.

[0099] Experimental Results

[0100] Reaction 1:

[0101] 3Li4P2S6+3S+Li2S=2Li7P3S 11

[0102] The Bragg peaks observed in the XRD pattern of Example 1 show correlation with the simulated peak positions of crystalline Li4P2S6 [1], as Figure 1 As shown. Figure 3 In the Raman spectrum of Example 1, the center is at 383 cm -1 The only peak is due to P2S6 4- Vibration of the PS bond in the anion [2,3]. Therefore, the sample was considered to be phase pure and was used as a precursor in reaction 1.

[0103] Reaction 1 was carried out via a mechanochemical synthesis route, and the reaction product was named Example 2. Figure 1 As shown, the product is X-ray amorphous, which indicates that the reagents were successfully amorphized. It is known from the literature that when Li2S (<75at%) and P2S5 are used as reagents for the mechanochemical synthesis of Li-PS compounds, the reaction leads to the formation of X-ray amorphous products, similar to the case of Example 2 [4-10]. Until now, the synthesis of Li-PS compounds (i.e., Li7P3S6) using different Li-PS compounds (i.e., Li4P2S6) as precursors has never been reported. 11 )[6-10].

[0104] After mechanochemical reaction, P2S7 4- and PS4 3- The vibration of the PS bond in the part appears in the Raman spectrum of Example 2, see Figure 2From P2S6 4- The sharp decrease in the signal intensity of the cell indicates that during the mechanochemical reaction, P2S6 4- Some of the phosphorus ions in the part are oxidized from +4 to +5. It is known that P2S7 4- The unit can be formed by reducing phosphorus at 280℃-300℃ to form P2S6 4- Unit [5,7]. Reaction 1 showed for the first time that this process can be reversed by a mechanochemical reaction.

[0105] The XRD pattern of Example 3 shows similarity to that of crystalline Li7P3S 11 The simulation pattern of

[11] , such as Figure 3 Other less intense peaks were observed at 17.3°, 24.5°, and 25.5°, which originated from the sample holder equipped with Be for collecting the pattern of the powder. Figure 4 The XRD pattern of Example 4 synthesized using Li2S and P2S5 as precursors is also shown in Figure 3 4 for comparison. Note some differences between Examples 3 and 4. There are sharper peaks in the pattern of Example 3, indicating a higher degree of crystallinity compared to Example 4. The lattice parameters of Examples 3 and 4 were obtained by curve fitting. The resulting fits and Bragg positions are shown in Figure 5 As shown. In the figure, the hollow circles represent the collected data, and the black line represents the resulting curve fit. Significant differences were observed in the curve parameters of Examples 3 and 4, and reference

[11] , see Table 1. Compared with Example 4 and the materials reported in the literature, the unit cell of Example 3 has a significantly shorter lattice parameter a and larger α angle and γ angle. It was observed that the β angle of Example 3 is larger than that of the literature example, but relatively smaller than the β angle of Example 4. These results demonstrate that the crystalline Li7P3S obtained by reaction 1 11 Structurally different from the materials synthesized by starting from the conventional reagents Li2S and P2S5.

[0106] Table 1: Lattice parameters of Examples 3 and 4 in the description of triclinic system P-1 and reported in the literature

[11]

[0107]

[0108] The Raman spectra of Examples 3 and 4 show that -1 、404cm -1 and 383cm -1 PS4 3- 、P2S7 4- and P2S6 4- Some bond vibrations, see Figure 2These results show correlation with those published in the literature [7,8,10,12-15]. In order to make a semi-quantitative comparison of the number of moieties in Examples 3 and 4, the spectra were fitted to three peaks centered at the reported positions of the structural moieties [5]. The relative ratios of the peak areas were also compared. Figure 6 and 7 As shown, the local structures of Examples 3 and 4 show significant differences.

[0109] PS4 in Example 3 3- / P2S7 4- The relative ratio of P2S6 was calculated to be 0.28, while the ratio in Example 4 deviated significantly and was recorded as 0.55. It was also observed that in the case of Example 3, P2S6 4- The relative intensity of the peak of the unit cell is 2.63% lower. These results clearly show that the materials synthesized from the reagents Li2S and P2S5 have different structural properties than those synthesized from different Li-PS compounds in the case of reaction 1.

[0110] The ionic conductivity of Examples 2, 3 and 4 is Figure 8 The activation energy was calculated from the σT vs. 1 / T plot using Equation 1, and the linear fit of the data for the calculated slope is also shown in Fig. 9 It shows:

[0111] Equation 1:

[0112]

[0113] Example 2 shows that at 20°C 5x 10 -5 S cm -1 The conductivity of Li7P3S is 0.40 eV. 11 After crystallization, Example 3 showed a significant increase in conductivity of 6 x 10 -4 S.cm -1 The activation energy for conduction is also reduced to 0.37 eV, which is less than the activation energy (0.38 eV) of Example 4 synthesized from precursors Li2S and P2S5. Example 4 has a conductivity of 9 x 10 -4 S cm -1 These results also show correlation with the values ​​reported in the literature [6, 14-18].

[0114] The results obtained from different characterization tools showed that crystalline Li7P3S 11 It can be synthesized by using the alternative synthetic route described in Reaction 1.

[0115] Compared with the values ​​reported in the literature and the crystalline Li7P3S synthesized by using Li2S and P2S5 as reagents 11 The obtained product according to the present invention (Example 3) shows significant differences in lattice parameters compared to the values ​​of (Example 4-Comparison). In addition, the relative ratios of the structural parts in Examples 3 and 4 are calculated to be significantly different. The impedance spectrum also shows that the ionic conductivity of the two examples is very similar to the materials reported in the literature. It is also noted that the successful reaction from one member of the Li2S-P2S5 binary system to another member has been reported in the literature for the first time. This discovery paves the way for finding other alternative reaction pathways between different members of the binary system.

[0116] References

[0117] [1] S. Neuberger, S. P. Culver, H. Eckert, W. G. Zeier, J. Schmedt auf der Günne, Refinement of the crystal structure of Li4P2S6 using NMR crystallography, Dalt. Trans. (2018). doi: 10.1039 / C8DT02619J.

[0118] [2] C. Dietrich, M. Sadowski, S. Sicolo, D. A. Weber, S. J. Seidlmaier, K. S. Weldert, S. Indris, K. Albe, J. Janek, W. G. Zeier, Local Structural Investigations, Defect Formation, and Ionic Conductivity of the Lithium Ionic Conductor Li4P2S6, Chem. Mater., 28 (2016), 8764-8773. doi: 10.1021 / acs.chemmater.6b04175.

[0119] [3] M. Tachez, J. Malugani, R. Mercier, R. Guy, Ionic conductivity of and phase transition in Li thiophosphate Li3PS4, Solid State Ionics. 14 (1984) 181-185. doi: http: / / dx.doi.org / 10.1016 / 0167-2738(84)90097-3.

[0120] [4] M. Tatsumisago, S. Hama, A. Hayashi, H. Morimoto, T. Minami, New lithium ion conducting glass-ceramics prepared from mechanochemical Li2S-P2S5 glasses, Solid State Ionics. 154 (2002) 635-640. doi: 10.1016 / S0167-2738(02)00509-X.

[0121] [5] C. Dietrich, D. A. Weber, S. J. Seidlmaier, S. Indris, S. P. Culver, D. Walter, J. Janek, W. G. Zeier, Lithium ion conductivity in Li2S-P2S5 glasses-building units and local structure evolution during the crystallization of superionic conductors Li3PS4, Li7P3S11 and Li4P2S7, J. Mater. Chem. A., 5 (2017), 18111-18119. doi: 10.1039 / C7TA06067J.

[0122] [6] Y. Seino, T. Ota, K. Takada, A. Hayashi, M. Tatsumisago, Asulphide lithium super ion conductor is superior to liquid ion conductors for use in rechargeable batteries, Energy Environ. Sci. 7 (2014) 627-631. doi: 10.1039 / C3EE41655K.

[0123] [7] Y. Seino, M. Nakagawa, M. Senga, H. Higuchi, K. Takada, T. Sasaki, Analysis of the structure and degree of crystallisation of 70Li2S-30P2S5 glass ceramic, J. Mater. Chem. A. 3 (2015) 2756-2761. doi: 10.1039 / C4TA04332D.

[0124] [8] Y. Aoki, K. Ogawa, T. Nakagawa, Y. Hasegawa, Y. Sakiyama, T. Kojima, M. Tabuchi, Chemical and structural changes of 70Li2S-30P2S5 solid electrolyte during heat treatment, Solid State Ionics. 310 (2017) 50-55. doi: 10.1016 / j.ssi.2017.08.006.

[0125] [9] K. Minami, A. Hayashi, M. Tatsumisago, Crystallization Process for Superionic Li7P3S11 Glass-Ceramic Electrolytes, J. Am. Ceram. Soc. 94 (2011) 1779-1783. doi: 10.1111 / j.1551-2916.2010.04335.x.

[0126]

[10] MRBusche,DAWeber,Y.Schneider,C.Dietrich,S.Wenzel,T.Leichtweiss,D. W. Zhang, H. Weigand, D. Walter, S. J. Seidlmaier, D. Houtarde, L. F. Nazar, J. Janek, In Situ Monitoring of Fast Li-Ion Conductor Li7P3S11 Crystallization Inside a Hot-Press Setup, Chem. Mater. 28 (2016) 6152-6165. doi: 10.1021 / acs.chemmater.6b02163.

[0127]

[11] H.Yamane,M.Shibata,Y.Shimane,T.Junke,Y.Seino,S.Adams,K.Minami,A.Hayashi,M.Tatsumisago,Crystal structure of a superionic conductor,Li7P3S11,Solid State Ionics.178(2007)1163-1167.doi:10.1016 / j.ssi.2007.05.020.

[0128]

[12] RCXu,XHXia,ZJYao,XLWang,CDGu,JPTu,Preparation ofLi7P3S11 glass-ceramic electrolyte by dissolution-evaporation method for all-solid-state lithium ion batteries,Electrochim.Acta.,219(2016)235-240.doi:10.1016 / j.electacta.2016.09.155.

[0129]

[13] M. Calpa, N.C. Rossero Navarro, A. Miura, K. Tadanaga, Preparation of sulfide solid electrolytes in the Li2S-P2S5 system by a liquid phase process, Inorg. Chem. Front. (2017). doi: 10.1039 / C7QI00737J.

[0130]

[14] Y. Wang, D. Lu, M. Bowden, P. Z. El Khoury, K. S. Han, Z. D. Eng, J. Xiao, J. -G. Zhang, J. Liu, Formation mechanism of Li7P3S11 solid electrolytes through liquid phase synthesis, Chem. Mater. (2018) acs.chemmater.7b04842.doi:10.1021 / acs.chemmater.7b04842.

[0131]

[15] M. Calpa, N.C. Rossero Navarro, A. Miura, K. Tadanaga, Preparation of sulfide solid electrolytes in the Li2S-P2S5 system by a liquid phase process, Inorg. Chem. Front. (2018) 501-508. doi: 10.1039 / C7QI00737J.

[0132]

[16] IH Chu, H. Nguyen, S. Hy, YC Lin, Z. Wang, Z. Xu, Z. Deng, YS Meng, S P O Ng, Insights into the Performance Limits of the Li 7 P 3 S 1 1 Superionic Conductor: A Combined First-Principles and Experimental Study, ACS Appl. Mater. Interfaces, 8 (2016), 7843-7853. doi: 10.1021 / acsami.6b00833.

[0133]

[17] S. Wenzel, D. A. Weber, T. Leichtweiss, M. R. Busche, J. Sann, J. Janek, Interphase formation and degradation of charge transfer kinetics between alithium metal anode and highly crystalline Li7P3S11 solid electrolyte, Solid State Ionics. 286 (2016) 24-33. doi: 10.1016 / j.ssi.2015.11.034.

[0134]

[18] S. Ito, M. Nakakita, Y. Aihara, T. Uehara, N. Machida, A synthesis of crystalline Li7P3S11 solid electrolyte from 1,2-dimethoxyethane solvent, J. Power Sources. 271 (2014) 342-345. doi: 10.1016 / j.jpowsour.2014.08.024.

Claims

1. A method for preparing a Li-PS product, the method comprising at least the following steps: (a) mixing at least Li4P2S6, Li2S and sulfur to obtain a first mixture; (b) heating the first mixture in an inert atmosphere, under vacuum or under a flow of H2S, and at a temperature of 150°C to 600°C for 1 hour to 200 hours to produce the Li-PS product; and (c) Cooling and optionally pulverizing the Li-PS product.

2. The method according to claim 1, wherein: The Li-PS product is selected from the group consisting of: Li7P3S 11 , Li3PS4, Li7PS6, and / or Li 9.6 P3S 12 .

3. The method according to claim 1 or 2, wherein: The temperature in step (b) is comprised between 180°C and 220°C.

4. The method according to claim 1 or 2, wherein: The heating in step (b) is carried out over a period of time comprised from 6 hours to 200 hours.

5. The method according to claim 1 or 2, wherein: Li4P2S6 is obtained from the reaction between Li2S and P2S5.

6. A Li-PS product obtained by the method according to any one of claims 1 to 5.

7. A kind of Li7P3S 11 A product having a crystalline structure and a volume V per formula unit comprised between 407 and 412 cubic angstroms at room temperature, measured by X-ray diffraction using a Bruker D8 diffractometer with CuKα radiation, and said volume V per formula unit being determined using unit cell parameters obtained at standard atmospheric pressure, wherein said product is obtained by the process of claim 1.

8. Use of the product according to claim 6 or 7, alone or in combination with any crystalline or amorphous conductive Li material, as a solid electrolyte.

9. A solid electrolyte comprising at least one product according to claim 6 or 7.

10. A battery comprising at least one product according to claim 6 or 7.

Citation Information

Patent Citations

  • Process for production of sulfide solid electrolyte material, and process for production of lithium solid-state battery

    CN102959646A

  • Sulfide solid electrolyte glass, lithium solid-state battery, and method For Producing Sulfide Solid Electrolyte Glass

    CN103052995A